2013
DOI: 10.1103/physrevd.88.023531
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on coupled dark energy from the Planck satellite experiment

Abstract: We present new constraints on coupled dark energy from the recent measurements of the Cosmic Microwave Background Anisotropies from the Planck satellite mission. We found that a coupled dark energy model is fully compatible with the Planck measurements, deriving a weak bound on the dark matter-dark energy coupling parameter ξ = −0.49−0.31 at 68% c.l.. Moreover if Planck data are fitted to a coupled dark energy scenario, the constraint on the Hubble constant is relaxed to H0 = 72.1 +3.2 −2.3 km/s/Mpc, solving t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
131
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(163 citation statements)
references
References 54 publications
31
131
1
Order By: Relevance
“…IV, baryons, DM and DE interact only indirectly by gravitation (via the Poisson equation). However, DE may interact with DM non-gravitationally, via a reciprocal exchange of energy and momentum; thus, is called interacting DE (IDE) [7,73,[109][110][111]. In this section we probe the magnification angular power spectrum for an IDE scenario-assuming (hereafter) a latetime universe dominated by DM and DE only.…”
Section: The Power Spectrum With Interacting Dark Energymentioning
confidence: 99%
“…IV, baryons, DM and DE interact only indirectly by gravitation (via the Poisson equation). However, DE may interact with DM non-gravitationally, via a reciprocal exchange of energy and momentum; thus, is called interacting DE (IDE) [7,73,[109][110][111]. In this section we probe the magnification angular power spectrum for an IDE scenario-assuming (hereafter) a latetime universe dominated by DM and DE only.…”
Section: The Power Spectrum With Interacting Dark Energymentioning
confidence: 99%
“…It has been suggested that a different dark sector interaction may be able to resolve the tension (Salvatelli et al 2013(Salvatelli et al , 2014Costa et al 2014;Murgia et al 2016). As a simple test, we apply the geometrical probes to a particular coupled dark energy and dark matter model which has the interaction term proportional to the dark energy component Q = ξHρ DE .…”
Section: Gcgmentioning
confidence: 99%
“…It is also important to compare our results (and those of [44]) with those obtained for DE models or similar CDM-DE mixtures in FLRW cosmologies [1,2,7,8,[13][14][15][16]48,49], since the dynamics of LTB solutions described by q-scalars and their fluctuations can be mapped to linear perturbation on an FLRW background [40]. While the spherical symmetry of the LTB models allows for the description of a single structure, the evolution of the latter can be studied exactly throughout the full non-linear regime.…”
Section: Discussionmentioning
confidence: 75%
“…In [6,13,14] and for a similar coupling term with positive defined coupling constant, the authors find that the observational data suggest that α is smaller than 0.003 to 1σ , and smaller than 0.01 to 2σ , while a value of order 0.1 is ruled out at better than 99.95%. On the other hand, in [49] the evolution of linear perturbations in a FLRW background sharing our assumptions on CDM, DE and J q leads to the bounds − 0.22 > 3α > − 0.90 to comply with the constraints of CMB anisotropy. These results are specially interesting, since the dynamics of LTB solutions described by q-scalars and their fluctuations can be mapped to linear perturbation on an FLRW background [40].…”
Section: Critical Points In Terms Of the Parameters W And αmentioning
confidence: 74%